Understanding of cervical cancer, acceptability of HPV self-collection, and prevalence of HPV in a semi-urban setting in Bangladesh. - Lilah Khoja; Yuting Wang; Syed Emdadul Haque; Habibul Ahsan; Tariqul Islam; Saif Ullah Munshi; A K M Rabiul Hasan; Md Tariqul Islam; Alaya Begum Jharna; Celeste Leigh Pearce (Public Library of Science (PLoS), 2024)
Human Papillomavirus (HPV) self-sampling has been implemented successfully as an alternative to traditional forms of cervical cancer screening in low-resource settings. Through Bangladesh's current national cervical cancer screening program, only about 10% of the at-risk population is reached. Thus, Bangladesh is an ideal setting to consider HPV self-sampling to improve cervical cancer prevention efforts. However, the feasibility and acceptability of HPV self-sampling has not been evaluated in Bangladesh. We aimed to understand levels of HPV and cervical cancer knowledge and to evaluate the feasibility and acceptability of HPV self-sampling for cervical cancer screening in a semi-urban Bangladeshi community. Participants were recruited from a local clinic; 164 women completed a cross-sectional questionnaire about attitudes towards screening, and cervical cancer and HPV risk factor knowledge, and provided self-collected cervical samples for high-risk HPV testing. Of the participants, 4.3% tested positive for high-risk HPV and were referred for appropriate follow-up care. Nearly all participants had heard of cervical cancer, though specific knowledge was quite low. Self-sampling for high-risk HPV testing had high rates of acceptability, high rates of convenience, and very little discomfort and embarrassment reported in this study population, making implementing HPV self-sampling as a form of cervical cancer screening in Bangladesh appear feasible.